2002
DOI: 10.1021/jp025544x
|View full text |Cite
|
Sign up to set email alerts
|

Fe2O3 Nanoparticle Structures Investigated by X-ray Absorption Near-Edge Structure, Surface Modifications, and Model Calculations

Abstract: The structures of Fe 2 O 3 nanoparticles with different sizes were investigated using Fe K-edge X-ray absorption near-edge structure (XANES) and the FEFF calculations, as well as surface modification with enediol ligands. The studies not only revealed the existence of under-coordinated Fe sites in the nanoparticles but also confirmed that these under-coordinated sites were located on the surface. Upon binding of enediol ligands, surface sites were restructured to octahedral sites. In particular, the nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
199
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(219 citation statements)
references
References 31 publications
(49 reference statements)
14
199
1
2
Order By: Relevance
“…18 18,39 This will occur mostly in the surface region of the nanoparticles, where the probability of the creation of vacancies is higher. 18 Based on the earlier theoretical study 40 and XAS measurements 41 of nanoparticles, we suggest that the presence of the Fe 3+ ͑O h ͒ ions is due to excess oxygen at the surface of the nanoparticles. According to the literature about the molecular dynamics simulations of Fe 2 O 3 nanoparticles, 40 to achieve local charge neutrality, it is expected that oxygen atoms have a tendency to concentrate on the surface of the ZnO:Fe nanoparticles.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…18 18,39 This will occur mostly in the surface region of the nanoparticles, where the probability of the creation of vacancies is higher. 18 Based on the earlier theoretical study 40 and XAS measurements 41 of nanoparticles, we suggest that the presence of the Fe 3+ ͑O h ͒ ions is due to excess oxygen at the surface of the nanoparticles. According to the literature about the molecular dynamics simulations of Fe 2 O 3 nanoparticles, 40 to achieve local charge neutrality, it is expected that oxygen atoms have a tendency to concentrate on the surface of the ZnO:Fe nanoparticles.…”
Section: Resultsmentioning
confidence: 71%
“…If there are excess oxygen atoms, the Fe ions in the surface region of the ZnO:Fe nanoparticles would be coordinated to a larger number of oxygen atoms as if they were at the O h sites. Indeed, Chen et al 41 have reported that Fe͑T d ͒ ions in the surface region of Fe 3 O 4 nanoparticles have a tendency to be converted to Fe͑O h ͒. Note that the presence of Fe͑O h ͒ ions due to interstitial impurities has been excluded by EPR, XRD, and Mössbauer measurements on the same sample.…”
Section: Resultsmentioning
confidence: 98%
“…2 shows the normalized XAFS and XANES (inset) spectra for bare and starch-stabilized Fe 3 O 4 particles. The peak at 7.112 keV is attributed to quadrupole transitions from the 1s to 3d orbitals (Wilke et al, 2001;Chen et al, 2002). The peak at 7.132 keV shows the d-p hybriding between the metal atoms and ligands through bonding and multiple scatterings involving the same atoms with different scattering paths (Ankudinov et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…2A), the pre-edge peak around 7110 eV is attributed to the quadrupole transition from 1s to 3d orbital [42,43]. The absorption K-edge at 7122 eV does not show any obvious energy shift, indicating that the substitution of Mn cations does not affect the valences of iron cations.…”
Section: Xafs Spectroscopymentioning
confidence: 96%